The Socialist People's Libyan Arab Jamahiriya : 2005 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation underlies that in 2004, Libya's macroeconomic performance was satisfactory, owing mainly to higher oil prices and increased oil output. Real GDP grew 4 1\2 percent while consumer prices declined. The favorable developments in the oil market contributed to a significant improvement in the external current account surplus, which reached some 24 percent of GDP. In 2005, macroeconomic performance remained relatively strong. Real GDP growth was about 3 1\2 percent, and inflation low. In contrast to previous years, economic growth is estimated to have been generated mainly in the non-oil economy.